Impacts of Deepwater Horizon oil and associated dispersant on early development of the Eastern oyster Crassostrea virginica. Issue 1 (15th November 2015) - Vignier, J.; Donaghy, L.; Soudant, P.; Chu, F.L.E.; Morris, J.M.; Carney, M.W.; Lay, C.; Krasnec, M.; Robert, R.; Volety, A.K.
Abstract: The explosion of the Deepwater Horizon (DWH) oil platform resulted in large amounts of crude oil and dispersant Corexit 9500A® released into the Gulf of Mexico and coincided with the spawning season of the oyster, Crassostrea virginica . The effects of exposing gametes and embryos of C. virginica to dispersant alone (Corexit), mechanically (HEWAF) and chemically dispersed (CEWAF) DWH oil were evaluated. Fertilization success and the morphological development, growth, and survival of larvae were assessed. Gamete exposure reduced fertilization (HEWAF: EC201 h = 1650 μg tPAH50 L − 1 ; CEWAF: EC201 h = 19.4 μg tPAH50 L − 1 ; Corexit: EC201 h = 6.9 mg L − 1 ). CEWAF and Corexit showed a similar toxicity on early life stages at equivalent nominal concentrations. Oysters exposed from gametes to CEWAF and Corexit experienced more deleterious effects than oysters exposed from embryos. Results suggest the presence of oil and dispersant during oyster spawning season may interfere with larval development and subsequent recruitment. Highlights: C. virginica gametes and embryos were exposed to oil and/or Corexit for 96 h. Adverse effects occurred during fertilization and early development. At equivalent nominal concentrations, CEWAF (oil+Corexit) and Corexit alone induced similar toxic responses to early life stages. Presence of oil and dispersant during oyster spawning season may interfere with subsequent recruitment.